URGENSI HAK IMUNITAS PENDAMPING KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DALAM PROSES PERADILAN - Abdul Ismail; MD Shodiq; Mohamad Ismed (CORPUS JURIS : JURNAL ILMU HUKUM, 2025)
This study aims to find out how the implementation of the right to immunity of victims in the crime of sexual violence; and to find out how urgent it is to implement the provisions of the right to immunity of victims in the ideal sexual assault crime in the future. The method used in this study is normative legal research conducted as an effort to obtain the necessary data in relation to the problem. This research uses a legal approach (Statute Apporach), a conceptual approach, an analytical approach, a case approach (Case Approcah) and a comparative approach which in principle are sourced from primary legal materials, secondary legal materials, and tertiary legal materials with qualitative legal material analysis techniques The results of the study show that the right to immunity of the victim's companion is declarative and has not provided real protection. The main factors include weak technical arrangements, lack of understanding of law enforcement officials, a formalistic perspective that favors the victim, and a patriarchal culture that worsens the position of companion. Cases of criminalization, intimidation, and obstruction such as LBH Yogyakarta, UNRI, and UPTD PPA Makassar confirm that the permaping is still in a vulnerable position. Therefore, the implementation of the right to immunity for victims of sexual abuse in Indonesia has not been effective and requires strengthening regulations, increasing the capacity of the apparatus, clear operational protection, and changing the legal culture so that the criminal justice system is truly responsive and on the side of the victim.